(untitled) (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2025)
The EQUAL – European Qualification: Refugees and Recognition project, led by HK-dir (the Norwegian Directorate for Higher Education and Skills), works to strengthen fair and transparent recognition of refugees’ qualifications across Europe. Building on previous Erasmus+ initiatives, EQUAL focuses on supporting ENIC (European Network of Information Centres) and NARIC (National Academic Recognition Information Centres) through training, supervision, and shared methodologies for credential assessment. The project website provides an overview of its objectives, participating partners, and activities that promote inclusive recognition practices for displaced persons. Highlights include whitepapers focused on Romania, Poland, and Lithuania and videos of presentations from the project’s final dissemination conference, Bridging the Gaps: Rethinking Recognition to Ensure Equal Opportunities for Refugees, which took place at Norway House in Brussels on 3 December 2024. Citation Norwegian Directorate for Higher Education and Skills. (2025). EQUAL – European qualification: Refugees and recognition. https://hkdir.no/en/equal